INOVASI DIGITALISASI UMKM KOPI MELALUI SISTEM E-COMMERCE BERBASIS WEB PADA WARUNG KOPI GARASI NDESO - Fatkhurrochman, Fatkhurrochman; Wibowo, Teguh Hadi; Arifah, Fatimah Nur; Yusnanto, Tri; Kapti, Kapti; Muin, Muhammad Abdul (TRANSFORMASI, 2025)
The rapid development of digital technology has significantly impacted various sectors, including micro, small, and medium enterprises (UMKM). One of the most influential technological applications is the e-commerce information system, which facilitates online buying and selling activities without spatial and temporal limitations. This study aims to design and develop a web-based e-commerce system as a digitalization innovation for UMKM coffee businesses at Warung Kopi Garasi Ndeso, with the goal of expanding market reach and improving business management efficiency. The system development process adopts the Waterfall model, consisting of several stages: communication, planning, modeling, construction, and deployment. The system design employs Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD), while implementation utilizes the PHP programming language and MySQL as the database management system. System testing was carried out using the Blackbox Testing method to verify functionality, and user evaluation was conducted using the Likert scale involving 18 respondents, including the owner, admin, and customers. The testing results show that all system functions operate properly and meet user requirements. The user evaluation obtained a score of 647 out of 810 or 79.88%, indicating that the developed web-based e-commerce system has a good level of usability. Therefore, the implementation of digital innovation through this e-commerce system effectively supports Warung Kopi Garasi Ndeso in enhancing operational efficiency, expanding market reach, and strengthening the competitiveness of local coffee UMKM in the digital era.